DEVELOPMENT STRATEGY FOR THE CULTIVATION OF ORNAMENTAL PLANTS AND BONSAI EVERGREEN SHRIMP : (STUDY IN CV. LEBAT BERBUNGA IN JAYAPURA CITY’S HERAM DISTRICT) - Daniel A. Dawan; Agustinus Numberi (JOURNAL KOPERASI DAN MANAJEMEN, 2022)
Purpose – The purpose of the study was to determine the strategy for developing the Cemara Shrimp Bonsai ornamental plant and to discover what factors influence the business of the Cemara Shrimp Bonsai ornamental plant in Jayapura City’s Heram District. Design/methodology/approach – Technique data collection using observation, interview, documentation, and kuisioner. Analysis method the data used swot analysis done ( 4 ) the four that is the force strength, weakness, opportunities, threats. Findings – Lebat Berbunga in the abepura-sentani heram district city of Jayapura are in quadrant 2. It is stated that these attempts have the power and great chances of being developed in the future. The right marketing strategy is a strategy that supports policy and aggressive growth (growth-oriented strategy). This venture should focus on a strategy to increase the number of tanamanan evergreen bonsai shrimp and improve promotion to reach consumers. Research limitations/implications – There are several similar businesses in the city of Jayapura. the erratic, covid-19. and the absence of incentives and a policy of supporting business as an ornamental Originality/value – This is a nice company. strategic locationTechnological advancements are intertwined with collaboration with various parties. Market receptivity to new entrants in ornamental plants can be transformed. Keywords: DEVELOPMENT STRATEGY, BONSAI, SWOT Paper type: Case Study